Technology Blueprint Football Shoes Sensor / Muhammad Ihsan Mohd Danial - Mohd Danial, Muhammad Ihsan (2020)
Nowadays, we know all ages are eager to do exercise and concerned about their healthy lifestyle especially in football or rugby. Especially in football, before they play in the field they need football shoes. The point here we want to focus here is our football shoes sensor. Our football shoes sensor is designed to give more interest to a user to use the shoes to play a football. Our football shoes sensor focuses on 100% developed technology on football shoes while using a sensor. For our product, the mechanism and its objective are simple which is to provide a sensor on use and use a light material to ensure the shoes is light to run, comfortable to wear it and the shoes provide information to a user to give feedback about their gameplay.The football shoes sensor is an innovation of standard football shoes that do not have any sensor and a lot of lackness. The product is less costly and affordable compared to other technology like VAR(video assistant referee), chest chip sensor and video performance that record by performer analytic . VAR technology is an expensive technology. The target market for this product is the Sport shop, Sport center, Sport school and Project sport development center. This product is designed to counter the weather too like rain and snow because when the condition of the feel is wet and puddle, the shoes easily become heavy because they don't have water resistance. This technology will give new experience and easily develop a youth player.